'Care and Maintenance': Indigeneity, Disability and Settler Colonialism at the Canton Asylum for Insane Indians, 1902-1934 - Sarah Whitt (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: ableism; allotment; Canton Asylum; eugenics; Indigeneity; institutionalization; land expropriation; self-determination; settler colonialism; Western biomedicine